Epidemicity and Genotyping of Pediculus humanus capitis de Geer by Cytochrome Oxidase I gene among Syrian refugees dwelling some camps of Erbil, Kurdistan Region of Iraq - Hemdad H. Mawlood (Zanco Journal of Pure and Applied Sciences, 2022)
The objectives of the current study are to determine risk factors associated with the rampancy and molecular genotyping of the head lice (Pediculus humanus capitis de Geer) infesting Syrian refugees in some temporary camps of Erbil, Kurdistan region of Iraq. To meet the requirements of the study, some primary schools of refugee camps were chosen to collect the relevant data in the afore-mentioned city. The V-Comb trap method was used to obtain specimens of head lice from 202 students of both gender who attend refugee camp schools regularly. The analyzed data revealed that the prevalence rates of pediculosis among 6-10 and 11-15-year-old students were 69% and 64% respectively. The highest infestation rate (79%) was recorded among female students, whilst the lowest outbreak rate (61%) was detected among male students. Regarding the impact of hair lengths on the prevalence of the insect, the highest rate of infection (81.53%) was recorded for medium hair whilst the lowest rate (41.17%) was determined for long hairs. Concerning the hair posture factor, the rates of infestation were 100%, 73% and 55% for spring, straight, and wavy hairs respectively in the 6-10-year-old group. Ultimately, Genomic DNA extraction were performed and Mitochondrion Cytochrome Oxidase I gene was used successfully for PCR amplification and sanger sequencing for genotyping then submission of our query sequences to the NCBI GenBank .